2019
DOI: 10.1371/journal.pone.0211959
|View full text |Cite
|
Sign up to set email alerts
|

Second-line glucose-lowering drugs added to metformin and the risk of hospitalization for heart failure: A nationwide cohort study

Abstract: AimTo compare the risks of hospitalization for heart failure (HHF) associated with sulfonylurea (SU), dipeptidyl peptidase-4 inhibitor (DPP-4i), and thiazolidinedione (TZD) as add-on medications to metformin (MET) therapy using the data of Korean adults with type-2 diabetes from the Korean National Health Insurance database.MethodsWe identified 98,383 people who received SU (n = 42,683), DPP-4i (n = 50,310), or TZD (n = 5,390) added to initial treatment of MET monotherapy in patients with type-2 diabetes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…8 Regarding the sample size included, one-third of the total studies were designed as nationwide and population-based studies. [9][10][11][12][13][14][15][16] The findings of the included studies show that conventional ADDs, like metformin and S.U., were present in almost more than half of the comparisons with other ADD monotherapies. A relatively fewer number of studies were reported for SGLT2i, where only three studies investigated its associated CV outcomes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…8 Regarding the sample size included, one-third of the total studies were designed as nationwide and population-based studies. [9][10][11][12][13][14][15][16] The findings of the included studies show that conventional ADDs, like metformin and S.U., were present in almost more than half of the comparisons with other ADD monotherapies. A relatively fewer number of studies were reported for SGLT2i, where only three studies investigated its associated CV outcomes.…”
Section: Resultsmentioning
confidence: 98%
“…added to metformin conferred a higher risk of hospital hospitalisation compared to the DPP4i added to metformin. 16 Also, as monotherapies, DPP4i a safer ADD to be offered to diabetic patients with H.F. compared to glimepiride. 27 In a retrospective Korean cohort study, the findings suggested that Asian diabetic patients could have higher benefits, such as achieving average baseline blood glucose in patients with lower body mass index, by using DPP4i relative to other ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective cohort study in China, SUs monotherapy was significantly associated with a higher risk of heart failure compared with acarbose monotherapy for initial treatment of T2DM 6 . More evidence was seen in the Korean adults with T2DM, SU as an add‐on therapy to metformin may increase the risks of heart failure compared with dipeptidyl peptidase‐4 (DPP‐4) inhibitors 7 …”
Section: The Side Effects Of Sulfonylureasmentioning
confidence: 99%
“…In a recent meta-analysis with randomized controlled trials and observational studies, the use of DPP-4 inhibitors was not associated with increased risk of CV outcomes, including HHF, compared to the control group [ 9 ]. However, in a recent observational study with a nationwide database, the use of DPP-4 inhibitors as an add-on therapy to metformin was associated with a higher risk of HHF compared to sulfonylurea [ 10 ], while other studies have demonstrated that the use of DPP-4 inhibitors was associated with a lower risk of cardiovascular disease (CVD) events, including HHF, compared to the use of sulfonylurea [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%